Nonlinear Output Regulation with Input Delay and Application in AHV Attitude Control - Liang Cai; Qingxian Wu (International Journal of Aerospace Engineering)
Time delay phenomena exist almost everywhere in the actual world and are especially important in the control of an AHV. The small time delay usually ignored in control may cause quite obvious errors in the flight trajectory tracking, because of the extremely high flight speed. In this paper, a new framework of solving a nonlinear input delay regulation problem is proposed for the first time, which is comprised of nonlinear damping controllers, nonlinear disturbance observers, and a nonlinear time delay predictor-based compensator, under the proved separation principle. Then the attitude tracking control of an AHV with a known time-varying input delay is studied based on the proposed design framework. Simulation results show the advantage of the proposed control method.